Proline-rich Tyrosine Kinase 2 and Focal Adhesion Kinase Are Involved in Different Phases of Platelet Activation by vWF - Canobbio, Ilaria; Lova, Paolo; Sinigaglia, Fabiola; Balduini, Cesare; Torti, Mauro (Thrombosis and Haemostasis, 2002)
Stimulation of human platelets with von Willebrand factor (vWF) induces the rapid tyrosine phosphorylation of several proteins, but very little is known on the tyrosine kinases involved in this process. In the present work, we investigated and compared the activation of two related tyrosine kinases expressed in platelets: the proline-rich tyrosine kinase 2 (Pyk2) and the focal adhesion kinase (FAK). Both kinases were tyrosine phosphorylated upon vWF interaction with glycoprotein Ib-IX-V complex, but with different mechanisms. Tyrosine phosphorylation of FAK was totally dependent on thromboxane A2 production, and was inhibited by the integrin αIIbβ3 antagonist RGDS peptide. Moreover, chelation of intracellular calcium or inhibition of protein kinase C (PKC) totally blocked vWF-induced tyrosine phosphorylation of FAK, indicating that this event is downstream phospholipase A2 and phospholipase C activation. By contrast, tyrosine phosphorylation of Pyk2 was only partially reduced by aspirin and RGDS, and was not affected by either calcium chelation or PKC inhibition, suggesting that activation of this kinase does not require phospholipase-mediated signalling. Both FAK and Pyk2 translocated to the cytoskeleton upon vWF stimulation of human platelets by a mechanism depending on agonist-induced actin polymerisation. Prevention of cytoskeletal relocation of Pyk2 and FAK by cytochalasin D totally blocked vWFinduced tyrosine phosphorylation of both kinases. Finally, phosphorylation of Pyk2 induced by vWF, but not by thrombin, was inhibited by piceatannol, suggesting that this kinase lies downstream Syk. These results demonstrate that both Pyk2 and FAK are involved in platelet stimulation by vWF, but indicate that only Pyk2 may play a role in the early signal transduction events activated by ligand binding to glycoprotein Ib-IX-V.
Keywords: Platelets; tyrosine phosphorylation; von Willebrand factor; Pyk2; FAK